Managing volunteerism behaviour: the drivers of donations practices in religious and secular organisations - Abreu, M. E.; Laureano, R. M. S.; Sharifah, F. S. A.; Vinhas da Silva, R.; Dionísio, J. (Journal of General Management, 2015)
This paper investigates the key drivers of donations practices and offers insights into volunteerism behaviour in order to help charities make better informed decisions when attempting to attract more volunteers as well as helping them to better manage fundraising activities/practices. A framework is presented to test if gender, age, religious affiliation, compassion, altruism, egoism, and religiosity impact on the level of volunteerism of the donor. By using an email survey-method, this study is informed by 612 respondents who donate regularly to charitable institutions. The study finds that religiosity, altruism, and compassion boost the volunteerism level of the donor. The findings suggest that religiosity and religious affiliation positively influence the volunteerism of a donor, and so organisations can successfully look for volunteers among religiously affiliated groups who actively participate in religious services. Altruism and compassion are also important drivers for donor volunteerism and, as a result, organisations can develop volunteering campaigns and messages by portraying them as related to altruistic values and compassionate behaviours.